2010
DOI: 10.2495/hpsm100371
|View full text |Cite
|
Sign up to set email alerts
|

Development of statistical model to predict Raand Rzin laser cutting

Abstract: Laser cutting is one of the advanced machining methods for the material removing process. This paper explores the prediction model of the surface roughness (R a ) and roughness height (R z ) of laser beam cutting on acrylic sheets. The Box-Behnken design based Response Surface Method (RSM) was used to predict the effect of the laser cutting parameters, which are laser power, cutting speed and tip distance on R a and R z . The predictive models are in good agreement with the experimental results. The first orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Islam Shyha [11] investigated the the CO2 laser trimmg of the fibre reinforced plastics. The results showed that the material Removal Rate increased with the cutting speed and not on laser beam power or gas pressure settings.…”
Section: The Laser Cutting Processmentioning
confidence: 99%
“…Islam Shyha [11] investigated the the CO2 laser trimmg of the fibre reinforced plastics. The results showed that the material Removal Rate increased with the cutting speed and not on laser beam power or gas pressure settings.…”
Section: The Laser Cutting Processmentioning
confidence: 99%